Counterknowledge - Thompson, Damian (London, 2008)
We are being swamped by dangerous nonsense.From 9/11 conspiracy theories to Holocaust denial, creationism to alternative medicine, we are all experiencing an epidemic of demonstrably untrue descriptions of the world. For Damian Thompson, these unproven theories and spurious claims are forms of 'counterknowledge', and, helped by the internet, they are creating a global generation of misguided adherents who repeat these untruths and lend them credence. 'The sleep of reason brings forth monsters', warns the title of Francisco Goya's famous etching of 1799. As Damian Thompson demonstrates, unless the defenders of enlightenment values fight back soon, the counterknowledge industry has the potential to create new political, social and economic disasters.
Keywords: Terrorism